Assessment of extracranial metastatic disease in patients with brain metastases: How much effort is needed in the context of evolving survival prediction models?. (June 2021) - Nieder, Carsten; Mehta, Minesh P.; Guckenberger, Matthias; Gaspar, Laurie E.; Rusthoven, Chad G.; Sahgal, Arjun; Grosu, Anca L.; De Ruysscher, Dirk
Highlights: Survival prediction models are still evolving and imperfect. Some components of these models carry the risk of inter-observer inconsistency and time-dependent variation. Opportunities exist to enhance the assessment of extracranial metastases and potential surrogates. Abstract: Survival prediction models may serve as decision-support tools for clinicians who have to assign the right treatment to each patient, in a manner whereby harmful over- or undertreatment is avoided as much as possible. Current models differ regarding their components, the overall number of components and the weighting of individual components. Some of the components are easy to assess, such as age or primary tumor type. Others carry the risk of inter-assessor inconsistency and time-dependent variation. The present publication focuses on issues related to assessment of extracranial metastases and potential surrogates, e.g. blood biomarkers. It identifies areas of controversy and provides recommendations for future research projects, which may contribute to prognostic models with improved accuracy.